THE IMPORTANCE AND DIFFICULTIES OF LISTENING SKILL: A DESCRIPTION - Qaila Zulhairah Gultom; Putri Utari; Wiki Tedi Rahmawati (EXCELLENCE: Journal of English and English Education, 2023)
This article is a general description about the importance of listening skill and the difficulties that students may face in understanding listening skill. Thus, it is hoped that teachers can be more aware of listening skill which is as important as other language skills in learning and mastering foreign languages, especially English.